Association of visceral adiposity index with hypertension (NHANES 2003–2018) - Zhou, Haoran; Li, Tianshu; Li, Jie; Zheng, Dongdong; Yang, Jie; Zhuang, Xin (Frontiers in Cardiovascular Medicine, 2024)
Objectives: This study focused on the association between visceral adiposity index (VAI) and the prevalence of hypertension in a nationally representative population of American adults.The study obtained data from the National Health and Nutrition Exa mination Survey (NHANES) database from 2003 to 2018 for a large-scale stud y. This study incorporated participants ≥18 years of age. Multivariate logistic r egression modelling and smoothed curve fitting were applied to investigate the existence of a correlation between VAI and hypertension prevalence. Subgroups were analyzed to confirm the stationarity of the association between VAI and hypertension prevalence. In addition, an interaction test was conducted in this study.In completely adapted sequential models, the risk of hypertension prevalence in the overall population increased 0.17-fold with each 1-unit increase in VAI [odds ratio (OR) =1.17; 95% confidence interval (CI) 1.12-1.22]. In the wholly adapted categorical model, there was a 0.95-fold increased risk of hypertension in the population of VAI quartile 4 (Q4) versus VAI quartile 1 (Q1) (OR = 1.95; 95% CI 1.62-2.35). These results indicate that VAI was strongly related to the occurrence of hypertension, and smoothed curve-fitting analysis showed nonlinearity. Adjustment for covariates revealed no apparent interactions in the subgroup analyses, and results were stable across subgroups.This cross-sectional study suggests a nonlinear and positive correlation between elevated VAI and the adult risk of developing hypertension in U.S. adults.